Anti-inflammatory, gastroprotective and anti-ulcerogenic effects of red algae gracilaria changii (Gracilariales, Rhodophyta) extract - Shu, M.H.; Appleton, D.; Zandi, Keivan; AbuBakar, Sazaly (BMC, 2013)
Background: Gracilaria changii (Xia et Abbott) Abbott, Zhang et Xia, a red algae commonly found in the coastal areas of Malaysia is traditionally used for foods and for the treatment of various ailments including inflammation and gastric ailments. The aim of the study was to investigate anti-inflammatory, gastroprotective and anti-ulcerogenic activities of a mass spectrometry standardized methanolic extract of Gracilaria changii. Methods: Methanolic extract of Gracilaria changii (MeOHGCM6 extract) was prepared and standardized using mass spectrometry (MS). Anti-inflammatory activities of MeOHGCM6 extract were examined by treating U937 cells during its differentiation with 10 mu g/ml MeOHGCM6 extract. Tumour necrosis factors-alpha (TNF-alpha) response level and TNF-alpha and interleukin-6 (IL-6) gene expression were monitored and compared to that treated by 10 nM betamethasone, an anti-inflammatory drug. Gastroprotective and anti-ulcerogenic activities of MeOHGCM6 extract were examined by feeding rats with MeOHGCM6 extract ranging from 2.5 to 500 mg/kg body weight (b.w.) following induction of gastric lesions. Production of mucus and gastric juice, pH of the gastric juice and non-protein sulfhydryls (NP-SH) levels were determined and compared to that fed by 20 mg/kg b.w. omeprazole (OMP), a known anti-ulcer drug. Results: MS/MS analysis of the MeOHGCM6 extracts revealed the presence of methyl 10-hydroxyphaeophorbide a and 10-hydroxypheophytin a, known chlorophyll proteins and several unidentified molecules. Treatment with 10 mu g/ml MeOHGCM6 extract during differentiation of U937 cells significantly inhibited TNF-alpha response level and TNF-alpha and IL-6 gene expression. The inhibitory effect was comparable to that of betamethasone. No cytotoxic effects were recorded for cells treated with the 10 mu g/ml MeOHGCM6 extract. Rats fed with MeOHGCM6 extract at 500 mg/kg b.w. showed reduced absolute ethanol-induced gastric lesion sizes by > 99 (p < 0.05). This protective effect was comparable to that conferred by OMP. The pH of the gastric mucus decreased in dose-dependent manner from 5.51 to 3.82 and there was a significant increase in NP-SH concentrations. Conclusions: Results from the study, suggest that the mass spectrometry standardized methanolic extract of Gracillaria changii possesses anti-inflammatory, gastroprotective and anti-ulcerogenic properties. Further examination of the active constituent of the extract and its mechanism of action is warranted in the future.